La literatura infantil para el desarrollo del lenguaje de los niños de 3 a 4 años del programa Creciendo con Nuestros Hijos Ciudad Victoria. Periodo lectivo 2017- 2018 - Torres González, Thalia del Cisne (2018)
The present research work entitled: CHILDREN'S LITERATURE FOR LANGUAGE DEVELOPMENT IN CHILDREN AGED 3 TO 4 YEARS OLD FROM THE PROGRAM “CRECIENDO CON NUESTROS HIJOS CIUDAD VICTORIA”, ACADEMIC YEAR 2017- 2018, is a descriptive investigation which purpose is focused on knowing the characteristics of the variables to be investigated, as well as the causes and phenomena that intervene in the research problem. It has as a general objective to identify the influence of children's literature in the language development of children aged 3 to 4 years old from the program “Creciendo con Nuestros Hijos Ciudad Victoria”. The research methods used were: scientific method, analytical-synthetic method, descriptive method and statistical method, which allowed us to precisely develop this work. For data collection were employed some techniques such as: direct observation, structured interview and survey. The instruments applied were: Picture Vocabulary Test and observation guide for the children. These instruments helped to recognize the reality of children and their environment, in this way was possible plan an alternative proposal. The participants in this research were: 3 teachers, 12 parents and 12 children aged 3 to 4 years old. The application of the test and the observation guide enabled to identify the initial and final state of the children during the investigative process. At the conclusion of the research, it was recognized that children's literature has influence in the development of the child's language, since comparing the test and post-test a improvement were observed in the children, after the workshop carried out with them. Based on the foregoing, we recommend the planning of children's literature activities that enhance the development of language.influence